VD_FINDINFO HC / 2019 / 510 vom 7. Juni 2019 - VD Tribunal cantonal (2019)
CONTRAT DE TRAVAIL, RÉSILIATION, VACANCES, ACTION EN PAIEMENT | 329d CO, 335c CO, 106 al. 2 CPC (CH), 308 al. 1 let. a CPC (CH)